Material properties and explosive spalling of ultra-high performance concrete in fire - Li, Ye (2018)
Ultra-High Performance Concretes (UHPC) has high strength (greater than 150 MPa), high durability, and enhanced fracture energies due to its densely packed microstructure and very low permeability. However, these good features make UHPC more vulnerable to explosive spalling in fire condition. Explosive spalling is generally characterized by a forcible removal of pieces or layers of concrete from the heated surface of a structural element. It compromises the load-carrying capacity of structures because it involves loss of integrity of structures, loss of concrete cross section, and exposure of steel reinforcements to fire. Several mechanisms responsible for explosive spalling have been proposed by a number of researchers. However, the exact mechanism for spalling of UHPC is not yet widely understood or accepted. This work was aimed at investigating the behavior of UHPC at elevated temperature, especially explosive spalling of UHPC. The main factors involved are polypropylene fiber, polyethylene fiber, steel fiber, and aggregate size. Firstly, an experimental study was carried out to identify control UHPC matrix by Taguchi method. Secondly, residual mechanical properties of UHPC with PP fibers, steel fibers, and larger aggregates after exposure to elevated temperature (from 300 ℃ to 900 ℃) and after water quenching were investigated. Subsequently, the effects of polyethylene (PE)-steel fiber hybridization, water-to-binder ratio, and aggregate size on flexural performance of UHPC were investigated. The microstructure and phase change were investigated by means of field emission scanning electron microscope (FESEM) and X-ray diffraction (XRD). Thereafter, the focus was switched to transport properties of UHPC. The influence of aggregate size and inclusion of PP and steel fibers on the intrinsic permeability of UHPC at hot state was first investigated. Then, the effects of fiber fraction, geometry, and induced microcracks on the intrinsic residual permeability of UHPC were investigated in detail. A model was proposed to predict residual permeability of UHPC based on image processing and quantification of microcracks. In the last part, residual permeability was correlated to spalling extent of UHPC. Synergistic effects of combined polypropylene-steel fibers and combined polypropylene fiber-larger aggregate on explosive spalling prevention of ultra-high performance concrete (UHPC) were investigated. Microstructural analysis highlighted the connectivity of empty PP fiber tunnels through multiple microcracks. This is one of the main differences between UHPC and normal strength concrete.